Case Study : Muhammad Akmal Harith Bin Salman (Agent Rielkies) / Aimi Dalila Razani - Razani, Aimi Dalila (2021)
In this case study, I have learned a lot about business and how to be a good entrepreneurial. When doing this assignment, I got to know Encik Akmal who is agent Rielkies that I has been chosen to make him as my entrepreneurial. To be a successful entrepreneurial is not easy as we look at the social media. After I interviewed him, I realized that they had a lot of things to be facing and I proud of him. The target for his business is to give the best taste of chocolate for customers. This product is using premium chocolate with dry cranberry toppings. It is a type of food that can be enjoy to all people age. For the market target like what kind of customer that I choosing to sell my product is from young and adult generation. This because only this generations that have more interest with Rielkies. If I choosing to sell to old generation, it’s hard for me because some of them that does not have smartphone. Hard to communicate and promote to them. That’s why I choose young generation like teenagers and child also adult generation. Good features are also very much needed to be entrepreneurial. We need to be more patient and manage the time wisely. Manage customers fairly and be good. Do not easily giving up. Need to fight until the end. Confidents when promoting the product. Sometimes acquired new knowledge every day also good. I believe that he can achieve his goal one day. For conclusion, I got that to be an entrepreneurial is not something easy to do because they need to know more knowledge. They also need to be facing a lot of risk. I got so much information about business. The price that they make also need to be affordable to all people. When choosing the product that we want to sell also important because we want the best quality and the best choice.